Evaluation of the Policy for the Provision of Drainage Development Facilities and Infrastructure in Ketintang Village, Surabaya City - Auralia Salsabilla Yudi; Venus Soraya Rizky R. N; Fitria Dwi Anasari; M. Nabil Firzatulloh (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Flooding is a major urban problem in Surabaya, particularly in Ketintang Village, which frequently experiences significant water logging reaching depths of 20-25 cm. This study evaluates the effectiveness of drainage infrastructure development policies in Ketintang Village, Surabaya City, based on Mayor Regulation No. 68 of 2019 concerning the Implementation of Infrastructure Development Activities and Community Empowerment in Villages. The urgency of this research stems from the need to assess whether the implemented drainage policy has successfully addressed flooding issues and met community needs comprehensively. The research method used is a qualitative approach with a case study method. Data were collected through in-depth interviews with relevant stakeholders including village officials, the Department of Water Resources and Waste Management (DSDABM), and local community members, complemented by field observations and document analysis. Policy evaluation was conducted using William N. Dunn's six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results indicate that the drainage development policy shows positive outcomes across most evaluation criteria. The policy is effective in reducing flood frequency and duration, efficient in resource utilization through inter-agency coordination, and responsive to community needs through participatory planning processes. However, challenges remain in adequacy and equity aspects, as some areas have not been fully served due to land ownership issues and community resistance. The study recommends enhancing inclusive communication approaches, expanding drainage networks to underserved areas, integrating drainage policies with waste management and environmental education programs, and strengthening community participation to ensure equitable distribution of infrastructure benefits throughout Ketintang Village.